Linking maize farmers to market: a case study of private extension service in Yewa North Local Government Area of Ogun State, Nigeria - Ademola Adekunte Ladele; Jonathan Akinsola Akinwale; Benjamin Olusegun Oyelami (Journal of Agricultural Extension, 2016)
The challenges of feeding the world and ensuring sustainable livelihoods for small-scale farmers remain greater today than ever before. This is largely because efficient market systems and better coordinated commodity chains are rarely in place. There is therefore the need for shift from production-oriented agricultural extension services towards market orientation involving multi-stakeholder partnerships. This study therefore investigated how private extension services in Nigeria are responding to these needs. Using an explorative case study, this paper presents the activities of a private extension outfit along maize value chain in Ogun state, Nigeria. The study revealed that the outfit performs functions that are not limited to knowledge transfer but as well building integration and interaction among the diverse actors. The study further identified crucial performance indicators to evaluate success and ensure sustainability of the actors. Challenges such as breach of trust and sharp practices were also identified as obstacles to this approach. Meanwhile, the farmers were able to experience improved linkage to market as a result of the well coordinated maize value chain. These findings had therefore demonstrated on how private extension services in Nigeria is responding proactively to the pressure of changing roles and additional responsibilities on extension by rendering services that are not fully covered in public extension services.